The role of mir96 in predicting CTC status and prognostic evaluation in gastric cancer patients - Zheng, Qi; Ge, Haiyan (Cellular and Molecular Biology, 2024)
In this study, 20 patients clinically diagnosed with advanced gastric cancer were selected as subjects. Circulating tumor cells (CTCs) in the peripheral blood of gastric cancer patients were detected and counted by collecting peripheral blood samples at Ningbo No. 2 Hospital and using the Cell Rich TM system combined with a negative enrichment strategy. In addition, routine pathological examination and immunohistochemical staining were performed on surgical specimens, including HER2, EBER, E-cadherin, and vimentin indicators. These indicators were correlated and analyzed with CTC counts and routine clinical tests. At the same time, miRNA groups were performed to explore the miRNAs with or without correlation with CTC and to try to construct a predictive model for CTC status. Tumor tissue from patients whose CTC counts did not match the results of the miRNA prediction model was subjected to second-generation gene sequencing to analyze indicators such as tumor heterogeneity and immune microenvironment. The results of the study showed that CTCs were detected in the peripheral blood of 50% (10/20) of gastric cancer patients using the Cell Rich TM system, serum fibrinogen was negatively correlated with CTC counts, whereas TNM staging elements, HER2 receptor and p53 were not correlated with CTC counts. miRNA assays showed that the expression levels of miR218, miR1207, miR96, miR409, miR149, miR148a, miR155, miR370 and miR223 were significantly different between the two groups of CTC≥2 and CTC<2. Among them, miR-96 showed good efficacy as an indicator for predicting CTC status and assisting in determining the prognosis of gastric cancer. In conclusion, the present study demonstrated that the Cell Rich TM system combined with the negative enrichment strategy can effectively detect CTCs in the peripheral blood of gastric cancer patients and that the expression of miR-96 can be used as an effective indicator to predict CTC status and assist in determining the prognosis of gastric cancer. These findings have important implications for the diagnosis and treatment of gastric cancer and provide new clues for the further study of the tumor immune microenvironment and tumor heterogeneity.